Implementation of Cloud Native Architecture in PT XYZ's Accounting System - Tri Saputro, Tedy; Fathoni Aji, Rizal (The Indonesian Journal of Computer Science, 2024)
Microservices are commonly used as an architectural style in SaaS applications. Compared to monolithic architectures, they offer various advantages, such as fault tolerance mechanisms, scalability, and ease of customization. However, microservice architectures cannot stand alone. This is because microservices are based on distributed services and data isolation, and such systems will rely heavily on supporting infrastructure, Therefore, a cloud-native architecture is necessary, taking a philosophical approach to building applications that can fully leverage the cloud-native application model, with the microservice architecture style as one of the key components. This study delves into the integration of cloud-native architecture into the accounting system application of PT XYZ, an IT company specializing in consulting and software integration. The researcher examined the five elements of cloud-native architecture, evaluated them using the twelve-factor app, and identified areas for improvement for PT XYZ